Supplier Selection Using Fuzzy Analytical Hierarchy Process (FAHP) Method At PT. Gizitatapangan Sejahtera - Clarissa Angelina; Katlea Fitriani; Yeremias Budi Irawan (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2024)
The increasing demand for reliable supplier evaluation amidst economic recovery drives the need for an efficient decision-making process at PT. Gizitatapangan Sejahtera, particularly after operational disruptions during the pandemic. This study aims to identify critical criteria and prioritize suppliers for strategic collaboration using the Fuzzy Analytical Hierarchy Process (FAHP) method. Unlike traditional AHP, FAHP incorporates uncertainty in decision-making, providing a more robust evaluation framework. The research employed a mixed-method approach, combining interviews with company stakeholders and secondary data analysis. Six criteria—Quality, Cost, Delivery, Service, Long-term Relationship, and Flexibility—were evaluated through pairwise comparisons and transformed into fuzzy numbers. Results indicate Quality (0.358) and Cost (0.305) as the top priorities, with Supplier D emerging as the best choice, followed by Suppliers C, B, and A. Supplier D demonstrated superior performance in cost-effectiveness while maintaining quality standards, though its long-distance logistics posed challenges. This study underscores the importance of systematic supplier selection and provides actionable insights to enhance procurement strategies.